2003
DOI: 10.1074/jbc.m305456200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Proglucagon Transcription by Activated Transcription Factor (ATF) 3 and a Novel Isoform, ATF3b, through the cAMP-response Element/ATF Site of the Proglucagon Gene Promoter

Abstract: Glucagon, the second major glucose-regulated hormone in the control of glucose homeostasis, functions as a counter-regulator to insulin and is specifically produced by the pancreatic ␣ cells. Its excessive biosynthesis and secretion is associated with diabetes mellitus. The expression of the proglucagon gene has been demonstrated to be regulated by a cAMP-dependent pathway through cAMP-response element-binding protein (CREB) and possibly other transcription factors bound to its cAMP-response element (CRE)/acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 36 publications
2
37
0
Order By: Relevance
“…Furthermore, they were all detected in adult islets from PC2 null mice (23) and also in control islets, although Fra-1, c-Fos, and JDP-1 homologue levels were lower in both type islets; Maf K, Maf B, c-Jun, and JDP were detected at higher levels in PC2 null islets than in control islets, consistent with ␣ cell hyperplasia in this model (23). This subgroup deserves attention not only due to increasing evidence of their involvement in the regulation of glucagon and insulin gene transcription (30)(31)(32), glucose homeostasis (33), differentiation, and development (34,35); but also because of their rapid responses to environmental changes in vivo and in vitro as immediate-early response genes. The observed expression differences between ␣ and ␤ cells appear to be intrinsic and not due to in vitro artifacts.…”
Section: Rt-pcrsupporting
confidence: 48%
See 1 more Smart Citation
“…Furthermore, they were all detected in adult islets from PC2 null mice (23) and also in control islets, although Fra-1, c-Fos, and JDP-1 homologue levels were lower in both type islets; Maf K, Maf B, c-Jun, and JDP were detected at higher levels in PC2 null islets than in control islets, consistent with ␣ cell hyperplasia in this model (23). This subgroup deserves attention not only due to increasing evidence of their involvement in the regulation of glucagon and insulin gene transcription (30)(31)(32), glucose homeostasis (33), differentiation, and development (34,35); but also because of their rapid responses to environmental changes in vivo and in vitro as immediate-early response genes. The observed expression differences between ␣ and ␤ cells appear to be intrinsic and not due to in vitro artifacts.…”
Section: Rt-pcrsupporting
confidence: 48%
“…However, ATF3 overexpression in pancreas leads to defects in endocrine cell number and islet morphology (33). Our data suggest that ATF3 may have a prominent physiological role in ␣ cells of murine islets (32). Because c-Jun can inhibit insulin gene transcription by interfering with E2A products (40), differences in expression of c-Jun and E2A between ␣ and ␤ cells may contribute to the ␤ cell-specific expression of the insulin gene.…”
Section: Discussionmentioning
confidence: 91%
“…Although overexpression of Cdx-2 stimulates endogenous glu mRNA expression in the pancreatic InR1-G9 cells (41) but not in the intestinal GLUTag cells (40), the involvement of Cdx-2 in regulating basal glu mRNA expression in both pancreatic and intestinal cells cannot be excluded. Likewise, the paired homeodomain protein Pax-6 (39,40) and the protein kinase A signaling pathway (21,26,30,35) have been found to regulate glu gene expression in both pancreatic and intestinal proglucagonproducing cell lines, as well as in primary pancreatic islet and intestinal cell cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that the GLUTag cell line responds appropriately to the regulatory factors known to control glu gene expression and GLP-1 synthesis and secretion in primary gut endocrine cells, including cAMP/protein kinase A, glucose-dependent insulinotropic peptide, and bethanechol (26,40,50,51). Likewise, the ␣-TC-1 and InR1-G9 cell lines have been routinely used as ␣ cell models to study glu gene expression and glucagon synthesis and secretion (19,20,30,(52)(53)(54)(55)(56). In these cell lines, for example, glucagon secretion is repressed by retinol and retinoic acid (52) and activated by phorbol esters (54), cytosolic calcium oscillations are inhibited by high glucose, and glu mRNA expression and glucagon synthesis are inhibited by insulin (55).…”
Section: Discussionmentioning
confidence: 99%
“…Activation was subsequently attributed to a TCF binding site within the G2 enhancer element of the Gcg promoter and the production of TCF7L2 in the intestinal endocrine L cells [4]. It is well known that Gcg expression and GLP-1 production can be activated by elevations in cAMP levels [46][47][48][49][50][51][52]. Since the G2 enhancer element has been shown to mediate the stimulatory effect of both cAMP and calcium on Gcg promoter activity [53], it is possible that cAMP pathway cross-talks with the WNT pathway to regulate Gcg expression [12].…”
Section: Introduction To the Wnt Signalling Pathwaymentioning
confidence: 99%